Offshore cage systems: A practical overview - Scott D.C.B.; Muir J.F. (Mediterranean offshore mariculture, 2000)
A range of cage systems is now potentially available for offshore mariculture in the Mediterranean, though not all of these may prove to be effective in the intended environmental conditions and production regimes. The cost of installation and operation is also very critical. This paper provides an overview of the systems which are currently available, and based in particular on the authors' experience in developing and operating offshore projects, describes the relative advantages and disadvantages of each system. Finally, it provides a brief commentary on some of the critical design and operational factors which need to be addressed in the current generation of cage systems, to improve their effectiveness in the increasingly demanding production conditions of the marine aquaculture sector.
Advanced Course of the CIHEAM Network on Technology of Aquaculture in the Mediterranean on 'Mediterranean Offshore Mariculture', 1997/10/20-24, Zaragoza (Spain)